2017
DOI: 10.1158/1535-7163.mct-17-0439
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Secretase Inhibition by BMS-906024 Enhances Efficacy of Paclitaxel in Lung Adenocarcinoma

Abstract: Notch signaling is aberrantly activated in approximately one third of non-small cell lung cancers (NSCLC). We characterized the interaction between BMS-906024, a clinically relevant Notch gamma secretase inhibitor (GSI), and front-line chemotherapy in preclinical models of NSCLC. Chemosensitivity assays were performed on 14 human NSCLC cell lines. There was significantly greater synergy between BMS-906024 and paclitaxel than BMS-906024 and cisplatin (mean CI value = 0.54 and 0.85, respectively, P = 0.01). On a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…Moreover, the enhanced effects of crizotinib were slightly higher in the H1299 model, which is KRAS wildtype. This is in line with a recent publication which concluded that BMS-906024 not only sensitizes NSCLC to paclitaxel, but that this occurs more potently in KRAS and BRAF wildtype cancers therefore, possibly being able to predict better patient outcomes to dual combination therapy ( 19 ). On the other hand, other studies report that canonical NOTCH pathway is needed for the tumorigenesis of KRAS G12V driven NSCLC and that pharmacological inhibition with GSI arrests tumor growth partly via activation of DUSP1 and consequent dephosphorylation of ERK specifically (not MEK) ( 45 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the enhanced effects of crizotinib were slightly higher in the H1299 model, which is KRAS wildtype. This is in line with a recent publication which concluded that BMS-906024 not only sensitizes NSCLC to paclitaxel, but that this occurs more potently in KRAS and BRAF wildtype cancers therefore, possibly being able to predict better patient outcomes to dual combination therapy ( 19 ). On the other hand, other studies report that canonical NOTCH pathway is needed for the tumorigenesis of KRAS G12V driven NSCLC and that pharmacological inhibition with GSI arrests tumor growth partly via activation of DUSP1 and consequent dephosphorylation of ERK specifically (not MEK) ( 45 ).…”
Section: Discussionsupporting
confidence: 90%
“…NOTCH signaling has been shown to directly impact on the DNA damage response ( 15 ). Active NOTCH signaling has been linked, in different types of cancer, to resistance towards a broad range of chemotherapeutics and targeted agents, reviewed by Takebe et al ( 16 ), including cisplatin ( 17 ), docetaxel ( 18 ), paclitaxel ( 19 ), gefitinib ( 20 ), anti-HER2 (human epidermal growth factor receptor 2) ( 21 ), anti-estrogens ( 22 ), dasatinib ( 23 ), temozolomide ( 24 ), doxorubicin and melphalan ( 25 ). Chemotherapeutic resistance is linked to high NOTCH signaling in lung cancer stem cells and worse outcome ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the EMT-induced docetaxel resistance in these models is reversible or not, by blocking NOTCH, is not yet known. In a recent study, a small molecule γ-secretase inhibitor, BMS-906024, sensitized NSCLC cell lines to paclitaxel, and both drugs synergized preclinically by targeting the paclitaxel-induced increase in NOTCH1, especially in cell lines with a KRAS and BRAF wild-type background versus their mutant counterparts, in a TP53-dependent manner ( 100 ).…”
Section: Notch-related Resistance To Chemotherapymentioning
confidence: 99%
“…Given that NOTCH signaling is involved in the activation of both the RAS and PI3K signaling pathways, therapies targeting NOTCH in KRAS -driven tumors could be a promising strategy. In in vitro and in in vivo preclinical NSCLC models, GSI can increase paclitaxel sensitivity, particularly in KRAS -wild-type NSCLC, suggesting that KRAS / BRAF mutation status may predict combined efficacy of GSI with paclitaxel ( 100 ). Moreover, other studies have shown that GSI can suppress KRAS -driven NSCLC partly by suppressing ERK/MEK signaling by activating ERK phosphatase DUSP ( 153 ).…”
Section: Notch-related Resistance To Targeted Therapiesmentioning
confidence: 99%
“…Notch signalling is also involved in epithelial to mesenchymal transition during tumour progression and metastasis . Inhibition of Notch signalling often enhances the chemosensitivity of many tumours . Further, clinical findings suggest that Notch signalling impacts survival in human cancers .…”
Section: Importance Of Notch Signallingmentioning
confidence: 99%